Assessing the influence of obesity on longitudinal executive functioning performance in patients with obstructive sleep apnea syndrome. Issue 1 (January 2016) - Hilsendager, Chelsea A.; Zhang, Duan; McRae, Cynthia; Aloia, Mark
Summary: Objective: To investigate longitudinal performance on an executive functioning task among individuals with obstructive sleep apnea syndrome (OSAS) and the impact of obesity on performance. Methods: Participants completed the Trail Making Test Part B (TMT-B), which is an executive functioning task that measured cognitive flexibility, at baseline, 3-, 6-, and 12-month follow-ups. Hierarchical linear modeling (HLM) analyses were used to assess participants' initial performance on the task, as well the trajectories of growth on the task across time points. Additionally, body mass index (BMI) was included in the estimations of fixed and random effects as a predictor of performance. Results: There were no significant differences between obese and non-obese individuals on the cognitive flexibility task at baseline. However, obese and non-obese individuals differed significantly in their linear and quadratic rates of growth across time points. Conclusions: This study suggests that obese and non-obese individuals may differentially respond to Continuous Positive Airway Pressure (CPAP) treatment (as related to cognitive flexibility). Future research should examine the impact of weight loss on the neuropsychological sequelae of obese individuals with OSAS.